Assessment of high yielding varieties of rice (Oryza sativa) for integrated rice-fish-horticulture farming system under lowland ecosystem of north eastern India - Satapathy, B.S.; Singh, T.; Pun, K.B.; Rautaray, S.K. (Annals of Agricultural Research, 2014)
Field trials were conducted during 3 years from 2010-12 to assess the performance of high yielding varieties of rice for rice-fish-horticulture farming system under lowland rice ecosystem at Regional Rainfed Lowland Rice Research Station, Gerua, Asom. Among the rice varieties, Swarna performed better when water level was low during tillering stage. The new submergence tolerant variety Swarna sub-1 was not superior to Swarna when mean water depth remained below 40 cm. Ranjit,the popular high yielding variety for shallow lowland performed consistently better under ricefish system. Performance of tall and lodging susceptible varieties like Jalpriya and Mahsuri were inferior to semi-dwarf high yielding varieties under shallow low land situation. Rice varietySwarna recorded highest B: C ratio of 1.83 followed by Ranjit (1.82) and Swarna Sub1 (1.75).